63 Years and 715 Days to the "Boxed Warning": Unmasking of the Propylthiouracil Problem. (5th July 2010) - Rivkees, Scott A.
Abstract : 715 days after potential problems related to PTU use in children were presented in a debate in front of the Lawson Wilkins Pediatric Endocrine Society (LWPES), the US Food and Drug Administration issued a "black-box" warning about the hepatotoxicity risk of the antithyroid drug propylthiouracil (PTU). This safety advisory followed the collective actions of academic societies, medical publishers, the National Institutes of Health, and the FDA. Considering that surgery and radioactive iodine are the legitimate treatment options for Grave Disease (GD), and are now the preferred alternative therapy in individuals who developed toxic reactions to MMI, the use of PTU should now be limited to exceptional circumstances and pregnancy. Long-term PTU therapy, especially in children, is not justifiable. The current advisory comes 63 years after the introduction of PTU for clinical use in 1947.